Orunia, ul. Jedności Robotniczej 65-57 fot. Karol Nowaliński. - Nowaliński, Karol (1935- ). (1980)
Przedstawia kamienice nr 65-57 przy ul. Trakt Świętego Wojciecha (dawniej Jedności Robotniczej), ok. 1989 r.